Epistemology of the Use of Technology in Child Character Development in Demaan Kudus Village - Azka, Mohammad Noval; Sumadi, Eko; Sulaiman, Muhammad Noor (Jurnal Pendidikan Progresif, 2025)
Abstract: Epistemology of Technology Utilization in Child Character Development in Demaan Kudus Village. Objective: This study aims to explore the impact of technology utilization on the development of children's character in Demaan Village, Kudus, the role of parents in supervision, and recommend to parents and educational institutions in maximizing children's character development. Methods: This study uses a quantitative method, with a survey study approach through This research is carried out using a quantitative approach with a survey method. The research population is all residents of Demaan Kudus Village, sampling using the snowball sampling technique which includes 7 different RWs, from the total respondent data there are 55 respondents which include 23 female respondents, 32 male respondents. Questionnaires and interviews were used to collect data from research participants. The data was analyzed using a descriptive statistical method where questionnaires would be processed to determine the frequency and percentage, while the interviews would be analyzed qualitatively. Findings: In this digital age, children are exposed to a wide variety of technologies that not only affect the way they learn, but also shape their character and behavior. Demaan Village, as one of the areas in Kudus Regency that is adapting to technological advances, faces challenges and opportunities in utilizing technology to build the character of the younger generation. Conclusion: This study emphasizes that the use of technology can contribute positively to the development of children's character in Demaan Village, Kudus, as long as it is managed properly by parents and the community. An epistemological understanding of educational technology is needed to maximize the benefits while minimizing risks, so that children can grow into individuals of good character and ready to face challenges in the digital age. Keywords: epistemology, utilization of technology, character education.